Fermentative hydrogen production from microalgal biomass and agricultural wastes - Moura, Patrícia (2014)
Renewable, sustainable and carbon-neutral energy production is needed to deal with the challenges of the currently growing energy demand and deleterious climate changes. Hydrogen (H2) is presently seen as an ideal future energy carrier with technical, socio-economic and environmental benefits. H2 can be produced through biological conversion by photosynthesis, photo-heterotrophic and dark fermentation. The interest in biological hydrogen (bioH2) production has recently increased, as the traditional ways of H2 production are still costly and display a negative environmental impact. The research work on bioH2 production conducted at UB-LNEG targets the use of the most diverse feedstock biomass, process optimization and, whenever possible, integration under an energy-oriented biorefinery pathway. Microalgal biomass and agricultural wastes, such as carob pulp and chestnut shells, are excellent examples of non-food renewable biomass that we have already tested as potential feedstock for bioH2 production.